Small rodent species on pig and dairy farms: habitat selection and distribution - Lovera, Rosario (2019)
BACKGROUND: Rodent species are common in livestock production systems, and some of them are considered serious pests because of the sanitary problems and economic losses they cause. Information about microhabitat selection by rodent species in livestock production systems is necessary for understanding rodent requirements and to contribute to effective prevention and development of control measures for pest rodent species. In this work we study microhabitat selection by rodent species that inhabit pig and dairy farms in central Argentina. Rodent trapping was conducted over three years (2008–2011) on 18 livestock farms, each one sampled seasonally during one year. To study habitat selection, microhabitat characterizations were performed describing 22 environmental variables in captured sites and random trap sites without captures. RESULTS: With a trapping effort of 7333 Sherman and 7026 cage live trap-nights, 444 rodents of seven species were captured (including the murine pest species Rattus norvegicus, R. rattus and Mus musculus and four native species). The three murines selected characteristics related to building structure and/or to food sources availability/proximity, while Akodon azarae selected sites with tall herbatious vegetation. CONCLUSIONS: We identified microhabitat characteristics that explain habitat distribution of small rodent species in these complex farm systems. This study contributes to broaden the integrated pest management of rodent pest species and could also contribute to the reduction of the use of rodenticides in these systems.